Relationship between Symptoms of Depression and Anxiety with Major Adverse Cardiac Event in 7 days in Patients with Acute Coronary Syndrome in Cipto Mangunkusumo Hospital - Sari, Diah Pravita; Mudjaddid, E; Ginanjar, Eka; Muhadi, Muhadi (Jurnal Penyakit Dalam Indonesia, 2018)
Introduction. One of the causes of death in acute coronary syndrome is the occurrence of complication known as major adverse cardiac events (MACE). There are several predictors of the occurance of MACE in patients with ACS, including depression and anxiety. Thi study aimed to determine the association between depression and anxiety with major adverse cardiac events within 7 days in patients with acute coronary syndrome. Methods. Study with prospective cohort design to examine the association between depression and anxiety with MACE within 7 days of ACS patients, using HADS questionnaires on ACS patients undergoing treatment at ICCU, Hospitalization RSCM in January - May 2018. Bivariate analysis was performed to calculate the risk ratio (RR) of MACE occurrence within 7 days in the depression and anxiety group using SPSS. Results. Obtained number of subjects who meet the inclusion criteria of 114 people. Depression was obtained in 7% of subjects, Anxiety was obtained in 28,95% of subjects, and MACE was obtained in 9.6% of subjects. In the Depression group, MACE 7 days occurred in 12.5% of subjects. In the Anxiety group, MACE 7 days occurred in 21,2% of subjects. In bivariate analysis, Anxiety increased the risk of MACE within 7 days in patients with ACS, with relative risk (RR) of 4,2 (IK 1,34 – 13,70). Conclusions. Anxiety in patients with ACS is an independent predictor of MACE within 7 days and increases the risk of a 7 day MACE. There was no correlation between depression and MACE within 7 days in patients with ACS.